Effect of soil properties on phosphate desorption from some cultivated soils in arid region - Wahba, Monier M.; Zaghloul, Alaa M. (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Kinetics of soil chemical processes is one of the most important areas in environmental chemistry for metals availability in soils and mechanisms of desorption. Phosphorus (P) is one of the most important macronutrients that control plant growth and crop production. The present study aims to evaluate the influences of soil properties of Alluvial (Typic torrerets) and calcareous (Typic calcids) on the Kinetics of P desorption using batch and anion exchange resin techniques used for P adsorption, which is highly correlated with P uptake by growing plants. Results indicated that P desorption was best described by empirical modified Freundlich (power function) and Elovich equations and, to a lesser degree, by theoretical diffusion and first-order equations. The rate of P desorption from the alluvial soils was positively and highly correlated and largely controlled by clay content (r=0.96**) and surface area (r=0.87**), as indicated by the simple correlation coefficient and R2 in the multiple stepwise regression analysis. These soil properties largely controlled the variations in the kinetic parameters that describe the rate of P desorption and P intensity in the four tested kinetic models. On the other hand, calcium phosphate and active CaCO3 contents in the calcareous soils were negatively correlated. They largely controlled the variations in the rate and intensity parameters of the kinetic models. These results suggest that surface precipitation on the CaCO3 surface controls P desorption in calcareous soils, while reversibly, phosphate adsorption on the clay surface controls P desorption in the alluvial soils, which decreases in both cases, crop production.